Determinants of non-prescription antibiotic use and knowledge gaps in Indonesia: findings from the Indonesian Health Survey 2023 - Kusumaratna, Rina; Farsyah, Muhammad Athar (Universitas Gadjah Mada, 2025)
Purpose: This study examines the key determinants influencing non-prescription antibiotic use and identifies knowledge gaps in Indonesia, based on the 2023 National Health Survey (SKI 2023). Using national data, the research examines education, healthcare access, gender, and age-related trends, comparing these trends across rural and urban populations. Methods: The study utilizes SKI 2023 national data to analyze antibiotic usage patterns and examine trends related to education, healthcare access, public awareness, gender, and age. A comparative analysis of urban and rural areas reveals disparities, with Pearson Chi-Square and Multinomial Logistic Regression tests applied at p≤0.05 for statistical significance. Results: The study shows that lower education levels are significantly associated with higher antibiotic misuse (p<0.001). Younger individuals and males also tend to misuse antibiotics more frequently and have lower knowledge levels (p<0.001). In urban areas, 58.4% of males and 54.3% of females report using antibiotics without a prescription. Limited access to healthcare is also significantly linked to increased self-medication (p<0.001). Additionally, 73.5% of respondents hold misconceptions about antimicrobial resistance (AMR), underscoring the urgent need for improved public awareness and education. Conclusion: According to the Indonesian Health Survey 2023, non-prescription antibiotic use is more prevalent among individuals with lower educational attainment, younger age, male gender, urban residence, and limited access to healthcare. To address this issue, public policies should prioritize health education, school-based awareness programs, improved access to healthcare, and stricter regulation of antibiotic sales.